PRACTICES OF EDUCATION MANAGERS TO INCREASE TEACHERS' ENTHUSIASM FOR ACHIEVEMENT OF DESIRED RESULTS IN WORK - Abdul Shakoor; Muhammad Javed Iqbal (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The current study explored the practices of educational managers to increase teachers' enthusiasm for the achievement of desired results in work because educational managers and teachers are the important part of educational institutions and without their roles the academic performance cannot be achieved. The present study sought to analyse academic behaviour, personal behaviour, incentives, and contribution of educational managers for the institutional development through teachers' enthusiasm. It was a descriptive and co-relational study and the data were analysed through descriptive statistics, t-test, Pearson correlation, and regression. A questionnaire was used as a tool of the study which was validated by sending to the panel of experts and the reliability of the instrument was tested on Cronbach's alpha and Factor analysis. The population of the study was 279 educational managers and 3617 teachers while the sample of the study was 279 (100%) educational managers and 361 (10%) teachers. The sampling was made on census and simple random sampling. The findings of the study revealed that educational managers' practices towards teachers had weak correlation in motivation, boosting up morale, appreciation, task equal distribution, minimising communication gap, pointing out deficiencies in isolation, respect for teachers, cooperation, realising inner feelings, good conduct of behaviour, creating tension free and relaxed environment, sharing professional knowledge, introducing latest teaching techniques, making teachers energetic and efficient, promoting collegial and cooperative culture, formulating comprehensive school policy, acknowledgement of work contribution, and intervention in the staff duties. It is recommended for the educational managers to promote teachers' enthusiasm for the achievement of the desired result by enhancing motivation, democratic way of dealing, cooperation, and acknowledgement of their work.